Late results of endoscopic sphincterotomy for bile duct stones in elderly patients with gall bladders in situ. - Ingoldby, C J (1989)
Endoscopic sphincterotomy was undertaken in 186 patients with common bile duct stones and an intact gall bladder who were considered unfit for surgery. One hundred and seventy one patients had jaundice of whom 18 also had clinical cholangitis. The mean age of treated patients was 79.7 years (range 27-92) and only 13 were aged less than 60. Sphincterotomy was successful in 185 (99%) and complete clearance achieved in 172 (92.5%). Early complications occurred in nine patients (4.8%) of whom three died (1.6%). The patients have been followed on average for 32 months (range six to 72 months). Eighteen patients have subsequently required cholecystectomy (9.6%), with six major complications, but no deaths. There have been 27 natural deaths and 156 patients remain alive and symptom free. Endoscopic treatment alone is safe and effective in the majority of frail and elderly patients and can reduce the need for surgery in this high risk group.